Comparison of buprenorphine and pethidine given intravenously on demand to relieve postoperative pain. Issue 6195 (13th October 1979) - Chakravarty, K; Tucker, W; Rosen, M; Vickers, M D
Abstract : In a double-blind study of on-demand intravenous analgesia buprenorphine was found to be about 600 times as potent as pethidine. The incidence of side effects was similar with both drugs. The quality of analgesia, subjectively assessed, was good with both drugs using this method of administration. Provided that its low potential for abuse is substantiated, buprenorphine appears to be a powerful analgesic that may successfully be given intravenously on demand.